PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN PENDEKATAN SCIENTIFIC UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KELILING DAN LUAS LINGKARAN SMP NEGERI 13 PALU: Application Of The Quantum Teaching Learning Model With a Scientific Approach To Improve Student Learning Outcomes In The Material On The Circumference and Area Of Circles at SMP Negeri 13 Palu - Nadhila; Awuy, Evie; M, Bakri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to describe of the Quantum teaching Model with a Scientific approach that can improve Student Learning Outcomes in Class VIII B SMP Negeri 13 Palu on the material around and the Area of the Circle. This research is Classroom Action Research model by Kemmis and Taggart which consists of four stages, namely planning, implementing, observing, reflecting. This research was conducted in two cycles. In the first cycle the number of students who completed was 14 students with 58,33% completeness percentage and in the second cycle there were many student who completed 19 students with 76% completeness percentage. The result of observations of teacher activity in the good category and have increased in the second cycle in the very good category. The result of observation of student activities in the first cycle are in the good category and have increased in the second cycle in the very good category. The subjects of this study were 25 students and three were selected as infomants, the result showed that learning by collaborative learning models Quantum teaching with a scientific approach could improve student learning outcomes in class VIII B of SMP Negeri 13 Palu on the material around and the area of the circle, with six components namely : (1) Grow, (2) natural, (3) name, (4) demonstrate, (5) repeat, and (6) celebrate